Cell-cycle position of single MYC-driven cancer cells dictates their susceptibility to a chemotherapeutic drug - Ryl, Tatsiana; Kuchen, Erika; Shao, Chunxuan; Flórez, Andrés; Mönke, Gregor; Lamprecht, Florian; Höfer, Thomas (Cell systems, 2017)
Summary: While many tumors initially respond to chemotherapy, regrowth of surviving cells compromises treatment efficacy in the long term. The cell-biological basis of this regrowth is not understood. Here, we characterize the response of individual, patient-derived neuroblastoma cells driven by the prominent oncogene MYC to the first-line chemotherapy, doxorubicin. Combining live-cell imaging, cell-cycle-resolved transcriptomics, and mathematical modeling, we demonstrate that a cell's treatment response is dictated by its expression level of MYC and its cell-cycle position prior to treatment. All low-MYC cells enter therapy-induced senescence. High-MYC cells, by contrast, disable their cell-cycle checkpoints, forcing renewed proliferation despite treatment-induced DNA damage. After treatment, the viability of high-MYC cells depends on their cell-cycle position during treatment: newborn cells promptly halt in G1 phase, repair DNA damage, and form re-growing clones; all other cells show protracted DNA repair and ultimately die. These findings demonstrate that fast-proliferating tumor cells may resist cytotoxic treatment non-genetically, by arresting within a favorable window of the cell cycle.